Education Expenditure and Access to Education: Case Study of United Nations Educational, Scientific and Cultural Organization Declaration in Nigeria - Ebi, Bassey Okon; Ubi, Peter Samuel (International Journal of Economics and Financial Issues, 2017)
In recognition of importance of access to education, national leaders and international development agencies met in 1990 in Jomtien Thailand and committed themselves to universalizing access to primary schooling by 2000. Recognizing that the success of the access to education agenda requires a significant and well-targeted increase in financing, United Nations Educational, Scientific and Cultural Organization (UNESCO) declared a benchmark of at least 26% of total public expenditure to education. Nigeria despite being a member of UNESCO, allocates persistently below, 6% of her budget to education since the UNESCO Declaration in 1990. It is also worrisome to note that as at 2014, 40% of Nigerian children aged 6-11 do not attend any primary school, 30% of pupils drop out of primary school and only 54% transit to secondary schools (Federal Ministry of Education, 2014; and UNICEF, 2015). Could it be that, poor education spending is the reason for poor student's enrolment in Nigeria? If education spending had increased up to 26% of the total budget, is there reason(s) to believe that access to basic education will also increase and, if so, by how much? To answer these pertinent questions, secondary times-series data were obtained from both local and international sources and 26% allocation to education was projected from the existing total expenditure outlay for the period 1990-2015 in line with UNESCO declaration. Ganger causality tests was conducted and ordinary least square regression estimation technique was used in estimating the impacts from both actual education expenditure and that of projected 26% expenditure on access to all levels of education. The results point to three conclusions: First, there is strong and positive relationship between education expenditure and access to all levels of education in Nigeria. Second, 26% expenditure on education as prescribed by UNESCO would have had 19-times impact on access to primary school enrolment, more than 2-times impact on secondary school enrolment and 9-times impact on access to tertiary education, and on average 10-times access to all levels of education in Nigeria. Third, urbanization is symbiotic with access to education in Nigeria. Accordingly, the study recommended that that government should adhere to the UNESCO declaration of 26% budget allocation to education. Government should intensify urbanization of Nigeria enclaves by building infrastructures such as schools, hospitals, road network, markets, industries, etc. Keywords: Education Expenditure, School Enrolment, United Nations Educational, Scientific and Cultural Organization Declaration JEL Classification: H250